Lung capacity and alveolar gas diffusion in aquatic athletes: Implications for performance and health - García, I.; Drobnic, F.; Arrillaga, B.; Pons, V.; Viscor, G. (Apunts Medicina de l'Esport, 2021)
Background: The diffusion capacity of carbon monoxide (DLCO) provides a measure of gas transfer in the lungs. Endurance training does not increase lung volumes or diffusion in land-based athletes. However swimmers have larger lungs and better diffusion capacity than other matched athletes and controls. Purpose: The aim of this study was to evaluate pulmonary alveoli-capillary diffusion and lung volumes in elite aquatic athletes, specifically swimmers, artistic swimmers and water polo players. Methods: The participants were 64 international level aquatic athletes including 31 swimmers (11 female and 20 male), 12 artistic swimmers (only female), and 21 water polo players (10 female and 11 male). The single-breath method was used to measure DLCO and pulmonary parameters. Results: The main finding of this study is that DLCO is high in aquatic athletes, clearly above their reference values, both in females (33.4 ± 9.4 mL min-1·mmHg-1; 135%) and males (48.0 ± 5.83 mL min-1·mmHg-1; 148%). There was no difference in DLCO between female swimmers, artistic swimmers and water polo players (34.7 ± 8.3 to 33.4 ± 4.0 to 32.1 ± 5.6 mL min-1·mmHg-1), but male swimmers had a higher DLCO compared to water polo players (50.4 ± 5.3 to 43.4 ± 7.0, p = 0.014). Conclusions: Aquatic athletes have larger lungs and better diffusion capacity than the percentage predicted by age and height. Therefore, swimming-based sports could help to improve pulmonary function in many different segments of the population.